Harnessing the potential of therapeutic agents to safeguard bone health in prostate cancer. Issue 4 (November 2018) - Miller, Kurt; Steger, Günther; Niepel, Daniela; Lüftner, Diana
Abstract Background Patients with prostate cancer are at risk of impaired bone health. Prostate cancer has a propensity to metastasize to bone, after which patients are at risk of skeletal-related events (SREs). These complications are associated with increased mortality, substantial pain, and reduced quality of life. Patients are also at risk of bone loss due to androgen deprivation therapy (ADT), which can be compounded in elderly patients with reduced bone density. It is essential, therefore, that aspects of bone health and therapies able to prevent the occurrence of SREs are considered throughout the clinical course of prostate cancer. Methods We reviewed the literature regarding the molecular mechanisms underpinning bone lesion formation, the modes of action of therapies that prevent SREs, and the efficacy and safety of these therapies in patients with hormone-sensitive or castration-resistant prostate cancer (CRPC). Results Therapies such as denosumab (a RANKL inhibitor) and zoledronic acid (a bisphosphonate) were indicated for prevention of SREs. Radium-223 dichloride also has proven efficacy in delaying symptomatic SREs, as well as in improving overall survival through effects on bone metastases. Before development of bone metastases, low-dose denosumab may also be used for treatment of ADT-associated bone loss. Denosumab may also have the potential to delay bone metastases development in patients with CRPC, although this is not currently an approved indication. The safety profile of therapies to prevent SREs should be considered. This review consolidates the available evidence on use of denosumab and bisphosphonates in prostate cancer, differentiated by hormone-sensitive and castration-resistant disease. Conclusions There is convincing evidence to support the use of denosumab and bisphosphonates to maintain bone health in patients with prostate cancer. Clinicians should be mindful of the adverse event risk profile of these therapies.